Integrated pest management of economically important insects and pests of potato - Malik, Kamlesh; Bhatnagar, Anuj; Shah, M A; Naga, Kailash; Raghavendra, K V; Subhash, S (Indian Horticulture, 2020)
Potato production is often afflicted by a number of biotic and abiotic factors including insect pests of economic importance. Insects cause direct damage to leaves and tubers, and indirect damage by transmitting the viruses; which reduces both quality and yield of potato. The major insect pests attacking potato are aphids, whiteflies, leaf hoppers, thrips, white grubs, cutworms, potato tuber moth and mites. These insect pests can efficiently be managed by the methods described in this article.